MALNUTRITION-INFLAMMATION SCORE PREDICTS SURVIVAL IN HEMODIALYSIS PATIENS - Trajcheska, Lada; Arsov, Stefan; Selim, Gjulsen; Sikole, Aleksandar; Canevska, Aleksandra (Journal of Morphological Sciences; Vol 2 No 2 (2019): JMS, 2019)
The short life span of dialysis patients is induced by traditional cardiovascular and non-traditional dialysis related factors such as inflammation, oxidative stress, protein energy malnutrition. Malnutrition-Inflammation Score (MIS) has been proposed as a new quantitative system for assessment of malnutrition and inflammation. In this study we sought to investigate the association of MIS and five-year-mortality in dialysis patients. In a prospective study were included 131 prevalent dialysis patients. Kalantar-Zadeh method (7) was used to calculate the malnutrition score. Patients were followed for five years. Kaplan-Meier survival and Cox-proportional mortality analysis were performed according to higher and lower malnutrition inflammation score, by cut-off value of 7. The mean age of study participants was 55.45 years and mean dialysis vintage was 111.04 months. After follow-up of 60 months 55 (42%) patients died from all-cause mortality and out of those 65% (36) were cardiovascular deaths. In comparative analysis among the survived and died patients, none of the inflammatory or nutritional variables such as CRP, albumin, creatinine, BMI or SGA significantly differed. There was a significantly longer survival among patients with lower MIS in respect of all-cause and cardiovascular mortality [49.28 ±1.88 vs . 39.29±3.53 months, p=0.011], [52.20 ±1.7 vs . 45.07 ±3.41, p=0.045], respectively. MIS emerged as a powerful predictor of all-cause and cardiovascular mortality through Cox regression analysis: HR 1.97 95%CI:(1.15 – 3.38), p=0.013; HR 1.063 95%CI-0.952-1.186, p=0.055), respectively. The malnutrition-inflammation score is a useful tool to predict outcomes. The key to improving survival and quality of life in dialysis patients could be gained by understanding of the malnutrition-inflammation complex syndrome and its interactions with cardiovascular disease and outcome.